Nervione, a new benzofuran derivative from Nervilia concolor. Issue 20 (13th October 2022) - Tran, Cong-Luan; Tri, Mai Dinh; Tien-Trung, Nguyen; Phan, Nhat-Minh; Phan, Cam-Tu D.; Tran, Thanh-Nha; Do, Thanh-Hung; Tran, Nguyen-Minh-An; Tran, Thi-Ngoc-Mai; Duong, Thuc-Huy
Abstract: A new benzofuran derivative, nervione (1 ), was isolated from Nervilia concolor (Blume) Schltr. (Orchidaceae). Eight previously reported compounds were also isolated: 5, 7-dimethoxyflavone (2), 3, 5, 7-trimethoxyflavone (3), 7-methoxyflavone (4), 3, 7-dimethoxy-5-hydroxyflavone (5), tetramethylscutellarein (4', 5, 6, 7-tetramethoxyflavone) (6), 5, 7-dimethoxy-4'-hydroxyflavone (7), rhamnetin (8), and 5, 7-dihydroxy-3', 4'-dimethoxyflavone (9). The structures were elucidated by 1D, 2D NMR, and HRESIMS spectroscopy in addition to the literature. The relative configuration of 1 was defined using DP4+ probability while its absolute configuration was defined by comparison of the ECD spectrum of 1 with those of previously reported compounds. All isolated compounds were evaluated for alpha-glucosidase inhibition, revealing weak or no activity.